American travel literature, gendered aesthetics and the Italian tour, 1824-1862 - Bailey, Brigitte (Edinburgh critical studies in Atlantic literatures and cultures., 2018)
American Travel Literature analyses US tourist writings about Italy from 1824 to 1862 to explain what roles transatlantic travel, aesthetic response, and the genre of tourist writing played in the formation of the United States.